Intact high‐resolution working memory binding in a patient with developmental amnesia and selective hippocampal damage. Issue 8 (23rd June 2022) - Allen, Richard J.; Atkinson, Amy L.; Vargha‐Khadem, Faraneh; Baddeley, Alan D.
Abstract: Debate continues regarding the possible role of the hippocampus across short‐term and working memory tasks. The current study examined the possibility of a hippocampal contribution to precise, high‐resolution cognition and conjunctive memory. We administered visual working memory tasks featuring a continuous response component to a well‐established developmental amnesic patient with relatively selective bilateral hippocampal damage (Jon) and healthy controls. The patient was able to produce highly accurate response judgments regarding conjunctions of color and orientation or color and location, using simultaneous or sequential presentation of stimuli, with no evidence of any impairment in working memory binding, categorical accuracy, or continuous precision. These findings indicate that hippocampal damage does not necessarily lead to deficits in high‐resolution cognitive performance, even when the damage is severe and bilateral.